The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1149/1.1836953
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Oxidation of Methanol Using a New Base Electrocatalyst

Abstract: Preparation of a new electrocatalyst for the anodic oxidation of methanol in sulfuric acid is described.The catalyst shows a high degree of passivity in hot sulfuric acid, and a modest electrocatalytic activity toward the methanol reaction.Anodic oxidation of methanol, the reaction employed on the anode of the direct methanol fuel cell, is conventionally carried out using noble electrocatalysts. The best of these has been found to be a codeposited mixture of platinum and ruthenium. The use of base materials as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…In previous methods, where tungsten carbides (as well as other carbides) were produced by gas-phase reduction of W(VI) using methane/hydrogen mixtures, much carbon was also deposited [8][9][10][11], and this was detected by XRD. The advantage of this high-temperature solid-state synthesis is therefore the production of clean W 2 C/WC surfaces, without residual carbon coated on the surface: no carbon peaks were observed in the XRD patterns in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous methods, where tungsten carbides (as well as other carbides) were produced by gas-phase reduction of W(VI) using methane/hydrogen mixtures, much carbon was also deposited [8][9][10][11], and this was detected by XRD. The advantage of this high-temperature solid-state synthesis is therefore the production of clean W 2 C/WC surfaces, without residual carbon coated on the surface: no carbon peaks were observed in the XRD patterns in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Burstein). oxidation catalysis [7] and methanol electrocatalysis [8][9][10]. Sputtered nickel tantalum carbide has shown electrocatalytic activity as both an anode and cathode [11].…”
Section: Introductionmentioning
confidence: 99%
“…T ungsten carbide (WC) has been studied as a nonnoble anode electrocatalyst for acidic low‐temperature fuel cells. Experiments have been carried out using the material as an electrocatalyst for the anodic oxidation of hydrogen 1–4 and methanol 5,6 . The dimensions of the WC crystals influence the electrocatalyst performance; decreasing the WC particle size from 500 to 600 nm to 200 nm was reported to increase electrocatalytic activity significantly 3 .…”
Section: Introductionmentioning
confidence: 99%
“…WC has been proposed to partially or totally replace the noble metals like Pt to reduce the cost11121314151617181920212223242526. WC as catalyst was firstly used for alkane isomerization and showed a high catalytic activity which is comparable with Pt1011.…”
mentioning
confidence: 99%
“…Philip et al pointed out that the catalytic activity of WC on hydrogen oxidation was one hundred thousandth of Pt catalyst23. But the catalytic activity of WC on methanol oxidation was not so bad2425. Nakazawa et al reported that the electronegative WC could absorb the hydrogen in methanol, leading to the dehydrogenation and oxidation of methanol26.…”
mentioning
confidence: 99%